Decoding groundwater salinity using hydrochemical and isotopic techniques: A case study for Abulug River Basin, Philippines - C.B. Mata; L.A. Alejo; O.F. Balderama; J.L.R. Bareng; T.J.A. Mata; C.D.T. Racadio (Vietnam Journal of Earth Sciences, 2026)
Despite increasing evidence of groundwater salinization, the processes driving it and its geographic extent in the Abulug River Basin remain unexamined. Although complex methods exist, this study demonstrates that a simplified approach can yield meaningful insights into hydrological processes in the basin by combining findings from hydrochemical analysis, isotope techniques, and GIS mapping. Thirty-two sampling sites yielded 96 samples. Most of the samples exhibited similar behavior, except for a few. While the majority of the well samples in the research area are classified as Ca-Mg-HCO3, a recently formed groundwater with a short average residency period recharged by precipitation, a few samples exhibited the Na-Cl water type, which typically denotes salinization. Two river samples and seven well samples are within the mixing line. These samples are identified using the results from several ionic elements, ratios, and isotopic composition. Evolution diagrams, such as the Gibbs, Chadha, and Piper diagrams, suggested that seawater intrusion was not the only cause of salinization. The groundwater quality in the basin's coastal aquifer is deteriorating due to dominant salinization drivers, including seawater intrusion, paleo-saline groundwater, and rock-water interactions such as cation exchange, silicate weathering, and halite dissolution. It is recommended to prioritize policy implications for local managers, such as abstraction limits, integration of geophysical surveys, and sentinel network monitoring.